Metabolic profiling reveals altered tryptophan metabolism in patients with kawasaki disease - Fan, Xue; Li, Ke; Guo, Xin; Liao, Shengyou; Zhang, Qi; Xu, Yangkai; Cui, Hongtu; Zheng, Lemin; Xu, Mingguo (Frontiers in Molecular Biosciences, 2023)
Kawasaki disease (KD) is a childhood vasculitis disease that is difficult to diagnose, and there is an urgent need for accurate and specific biomarkers. Here, we aimed to investigate metabolic alterations in patients with KD to determine novel diagnostic and prognostic biomarkers for KD. To this end, we performed untargeted metabolomics and found that tryptophan (Trp) and tyrosine metabolism and phospholipid oxidation pathways were altered in patients with KD. Furthermore, tryptophan-targeted metabolomics was conducted to explore the role of tryptophan metabolism in KD. The results showed that Trp and indole acetic acid (IAA) levels markedly decreased, and L-kynurenine (Kyn) and kynurenic acid (Kyna) levels were considerably higher in patients with KD than those in healthy controls. Changes in Trp, IAA, Kyn, and Kyna levels in a KD coronary arteritis mouse model were consistent with those in patients with KD. We further analyzed public single-cell RNA sequencing data of patients with KD, revealing that their peripheral blood mononuclear cells showed aromatic hydrocarbon receptor expression that was remarkably higher than that of healthy children. These results suggest that the Trp metabolic pathway is significantly altered in KD and that metabolic indicators may serve as novel diagnostic and therapeutic biomarkers for KD.